1985
DOI: 10.1007/bf01966687
|View full text |Cite
|
Sign up to set email alerts
|

In vivo modulation of leukotaxis by non-steroidal anti-inflammatory drugs

Abstract: Since non-steroidal anti-inflammatory drugs (NSAIDs) are widely used for inhibition of inflammation, an in vivo assay for leukotaxis would be of use in comparing the biological activity effects of the agents. Here, the effects of 4 different NSAIDs on in vivo leukocyte accumulation was determined by quantitating N-formyl-methionyl-leucylphenylalanine induced leukotaxis in the rabbit anterior eye chamber. New Zealand white female rabbits were treated for three days with the following regimens: ibuprofen or aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…They are primarily mediated by inhibition of cyclooxygenase (COX)‐1 and COX‐2 activity . So far, the inhibitory effects of topical diclofenac formulations on leucocyte recruitment during inflammation have been described in several in vivo models, such as the corneal inflammation model in rabbits and the periodontal inflammation model in rats . In line with these previous analyses, we herein found that diclofenac‐containing gel effectively suppresses leucocyte adhesion and transmigration into inflamed tissue.…”
Section: Discussionsupporting
confidence: 86%
“…They are primarily mediated by inhibition of cyclooxygenase (COX)‐1 and COX‐2 activity . So far, the inhibitory effects of topical diclofenac formulations on leucocyte recruitment during inflammation have been described in several in vivo models, such as the corneal inflammation model in rabbits and the periodontal inflammation model in rats . In line with these previous analyses, we herein found that diclofenac‐containing gel effectively suppresses leucocyte adhesion and transmigration into inflamed tissue.…”
Section: Discussionsupporting
confidence: 86%